Comparing Sources of Location Data from Android Smartphones - Spreitzenbarth, Michael; Schmitt, Sven; Freiling, Felix (8th Annual IFIP WG 11.9 International Conference on Digital Forensics, 2012)
It is well-known that, for various reasons, smartphone operating systems persistently store location data in local storage. Less well-known is the fact that various network applications (apps) do this too. This paper considers the issue if location data extracted from mobile phones can replace or complement the location data obtained from network operators. Experiments with Android smartphones reveal that location data stored on the phones is often much more precise than the rather coarse-grained data stored by network operators. However, the availability of location data on smartphones varies considerably compared with the data stored by network operator
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lehrst.forens_9